Estrés laboral y su afectación psico-física en el rendimiento laboral de los trabajadores de la central de gestión operativa policial del distrito metropolitano de quito (cgop). Elaboración de una guia preventiva - Flores Brito, Pedro Renato (2018)
The situations that concern the health, are numerous, causing pressures that directly affect the integrality of the human being, the problem, perhaps the most noted in the last decades is the stress associated with the individuals work environment and how it is related to it. Stress has been studied a lot, but the environmental conditions of a workplace have always been put on the stage, this research considers other aspects that have to do with the perception of the health of the workers of a call center, for the role, importance and responsibility of having serenity at the moment of customer service, the ease of understanding and transmitting timely, clear and precise information, which in itself generates an anticipated anxiety, which originates, waiting for a call and the uncertainty of being able to be effective in that care. The research focuses on determining the psycho-physical impairment in work performance due to work stress, from the foundation of preventive health, associating the relationship between the two variables to verify their affectation, thus contributing to compliance with the law in institutions from the framework of occupational safety and risk prevention. Occupational stress influences the appearance of the psychophysical alterations that affect the work performance, since it has been verified in the investigated group that compose the Central Police Operating Management of the Metropolitan District of Quito workers using universal tests such as Maslach that measures burnout syndrome, fatigue emotional, depersonalization, and personal fulfillment are combined with Likert scales that measure the perception of those involved in their psychophysical involvement in their workplace.